1998
DOI: 10.1038/sj.onc.1201803
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma protein-overexpressing HL60 cells resistant to 1,25-dihydroxyvitamin D3 display increased CDK2 and CDK6 activity and shortened G1 phase

Abstract: Drug resistance that occurs during cancer chemotherapy has been a major problem in controlling neoplastic progression. To study the cellular mechanisms of acquired drug resistance we developed 1,25-dihydroxyvitamin D 3 (1,25D 3 )-resistant sublines of promyelocytic leukemia HL60 cells which have increased proliferation rates (Exp. Cell Res., 224, 312, 1996; Cancer Res., 50, 5513, 1996). We report here that the resistant sublines display varying degrees of shortening of the G1 phase as compared to the parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…3 a). CDK4 and CDK6 are, however, not functionally redundant and are differentially regulated by mitogenic signals (Laliberte et al, 1998 ;Wang et al, 1997Wang et al, , 1998. The pronounced restriction of both the catalytic and regulatory subunits of CDK4 and CDK6 complexes found in UV-MV-treated PBL might be sufficient to explain their reduced activity in vitro (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 a). CDK4 and CDK6 are, however, not functionally redundant and are differentially regulated by mitogenic signals (Laliberte et al, 1998 ;Wang et al, 1997Wang et al, , 1998. The pronounced restriction of both the catalytic and regulatory subunits of CDK4 and CDK6 complexes found in UV-MV-treated PBL might be sufficient to explain their reduced activity in vitro (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19]23 Expression of the markers of differentiation, on the other hand, showed little if any relationship to the levels of p27…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] These data, and additional studies of other cell cycle regulatory proteins, 23 indicate that a marked up-regulation of p27 Kip1 , with its subsequent attenuation upon resumption of cell growth, is characteristic of p27…”
Section: Long-term Exposure Attenuates the 125d 3 -Induced Elevationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results have indicated that the levels of p27 Kip1 were decreased, whereas those of cyclin D1, D2, D3, and E were elevated, in HL60 cells resistant to 1,25-dihydroxyvitamin D3 when compared with sensitive cells. 37,38 Accordingly, our HL60AR cells are resistant to ATRA 16 and displayed lower levels of p27 Kip1 and a higher amount of cyclin D1 when compared with ATRA-sensitive (PT) cells.…”
Section: Figurementioning
confidence: 99%